EFEKTIVITAS HUKUM PEMBERLAKUAN HAK IMUNITAS BAGI PEJUANG LINGKUNGAN HIDUP DI INDONESIA - Arifin, Ahmad; Setiyanto, Bagus Adek; Mubiin, Ajmal Nazirul; Fatahillah, Ikhwan Aulia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The purpose of this study is to explain the legal effectiveness of the immunity rights granted to environmental activists, as outlined in Law No. 32 of 2009 on Environmental Protection and Management, and to analyze the legal needs of environmental activists based on Lawrence Friedman’s legal system theory. This article employs a normative juridical research method, supported by theoretical and empirical approaches, where empirical data is obtained from actual facts or conditions regarding legal protection for environmental activists. The study results indicate that many environmental activists continue to face criminalization due to limited legal interpretation, a lack of understanding among law enforcement, and the strong influence of industry. Legal and procedural reforms, including the strengthening of the Anti-SLAPP concept, are needed to ensure that the fundamental rights of those advocating for the environment are protected and effectively enforced in practice.